Photoelectrochemical Water Splitting: Thermal Annealing Challenges on Hematite Nanowires - Quitério, P. (2020)
Hematite is getting great attention as an environmentally friendly material for photoelectrochemical water splitting, due to its narrow band gap (1.9-2.2 eV), nontoxicity, low cost, high stability and wide availability. However, hematite shortcomings such as its low absorption coefficient, short hole diffusion length, or poor electrical conductivity lead to multiple electron-hole recombinations and efficiency losses. This work describes the preparation of nanostructured hematite photoelectrodes by a hydrothermal method followed by thermal annealing under different conditions. A large spectrum of materials science characterization techniques were used to unify the broad and underlying physical-chemical processes by which a material's structure and properties influence the performance of these photoelectrodes. In particular, Sn diffusion into hematite via a high-temperature annealing scheme is fairly analyzed by Rutherford backscattering spectrometry to assess the in-depth Sn distribution profiles and by extended X-ray absorption fine structure analysis for structural order analysis. The increase of photocurrent with annealing temperature and time, besides being related with percent Sn diffusion along the hematite photoelectrode, is also correlated with nanowires morphology, porosity features, and structural crystalline order enhancement. This study shows that an accurate combination of the semiconducting photoelectrode intrinsic properties, such as percent Sn profile content, one-dimensional nanowire diameter, porosity, and structural crystalline order, naturally leads to photoelectrodes with improved conductivity to photogenerated carriers and reduced band gap.